Development of Six Sigma Infrastructure for Strabismus Surgeries - Taner, Mehmet Tolga; Sahbaz, Ibrahim; Kagan, Gamze; Atwat, Kamal; Erbas, Engin (International Review of Management and Marketing, 2013)
The purpose of this study is to show how a private eye care center in Turkey developed a Six Sigma infrastructure to investigate the root causes of complications occuring during strabismus surgeries. To analyze the collected data, main tools of Six Sigma’s Define-Measure-Analyze-Improve-Control (DMAIC) improvement cycle such as SIPOC table, Fishbone Diagram and, Failure, Mode and Effect Analysis were implemented. Patient’s eye anatomy, experience of the anesthesiologist, experience/attention of the strabismus surgeon was identified to be Critical-to-Quality (CTQ) factors for a successful strabismus surgery. The most frequent complications of strabismus surgeries were found to be X, Y and Z. The process sigma level was found to be 3.2025. Keywords: Six Sigma; ophthalmology; strabismus surgery; complications JEL Classifications: I120; L15